Europium (III) as a Circularly Polarized Luminescence Probe of DNA Structure - Wu, Tao; Bouř, Petr; Andrushchenko, Valery (Scientific reports, 2019)
We report as a proof-of-concept the first application of circularly polarized luminescence (CPL) measured with a Raman optical activity (ROA) spectrometer to differentiate several DNA structures without need of sensitizing complexes. The ROA/CPL approach provides sufficiently high CPL intensity to use hydrated Eu3+ ions, thus avoiding DNA structural changes associated with binding of sensitizers and overcoming the sensitizer quenching issue. We showed that deoxyguanosine monophosphate (dGMP), single- and double-stranded DNA provide different CPL spectra, which could be used for their discrimination. Our results demonstrate that ROA/CPL method is a promising approach to measure CPL spectra of complex biomolecules when the use of sensitizers is not possible. The method can be extended to other biomolecules, such as proteins, lipids, sugars, etc.
Keywords: Europium; Deoxyguanine Nucleotides; luminiscence; DNA; Luminescence; deoxyguaninnukleotidy; europium; Spectrum Analysis, Raman; Ramanova spektroskopie